Dysregulated long non-coding RNA in Sjögren's disease impacts both interferon and adaptive immune responses. Issue 2 (1st December 2022) - Joachims, Michelle L; Khatri, Bhuwan; Li, Chuang; Tessneer, Kandice L; Ice, John A; Stolarczyk, Anna M; Means, Nicolas; Grundahl, Kiely M; Glenn, Stuart B; Kelly, Jennifer A; Lewis, David M; Radfar, Lida; et al.
Abstract : Objective: Sjögren's disease (SjD) is an autoimmune disease characterised by inflammatory destruction of exocrine glands. Patients with autoantibodies to Ro/SSA (SjD Ro+ ) exhibit more severe disease. Long non-coding RNAs (lncRNAs) are a functionally diverse class of non-protein-coding RNAs whose role in autoimmune disease pathology has not been well characterised. Methods: Whole blood RNA-sequencing (RNA-seq) was performed on SjD cases (n=23 Ro/SSA negative (SjD Ro− ); n=27 Ro/SSA positive (SjD Ro+ ) and healthy controls (HCs; n=27). Bioinformatics and pathway analyses of differentially expressed (DE) transcripts (log2 fold change ≥2 or ≤0.5; padj <0.05) were used to predict lncRNA function. LINC01871 was characterised by RNA-seq analyses of HSB-2 cells with CRISPR-targeted LINC01871 deletion ( LINC01871 −/ − ) and in vitro stimulation assays. Results: Whole blood RNA-seq revealed autoantibody-specific transcription profiles and disproportionate downregulation of DE transcripts in SjD cases relative to HCs. Sixteen DE lncRNAs exhibited correlated expression with the interferon (IFN)-regulated gene, RSAD2, in SjD Ro+ (r≥0.65 or ≤−0.6); four antisense lncRNAs exhibited IFN-regulated expression in immune cell lines. LINC01871 was upregulated in all SjD cases. RNA-seq and pathway analyses of LINC01871 −/ − cells implicated roles in cytotoxic function, differentiation and IFNγ induction. LINC01871 was induced by IFNγ in a myeloid cell line and regulated by calcineurin/NFAT pathway and T cell receptor (TCR) signalling in primary human T cells. Conclusion: LINC01871 influences expression of many immune cell genes and growth factors, is IFNγ inducible, and regulated by calcineurin signalling and TCR ligand engagement. Altered LINC01871 expression may influence the dysregulated T cell inflammatory pathways implicated in SjD.